ANIMAL RIGHTS IN ISLAM AND CHRISTIANITY: AN ANALYTICAL AND COMPARATIVE STUDY - Sarwar, Dr Muhammad; Ashfaq, Dr Muhammad; Raza, Dr Ahmad; Shahzad, Aamir (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
This analytical and comparative study aims to explore and analyze the perspectives on animal rights in Islam and Christianity, two of the world’s major religions. The treatment of animals and their rights within religious frameworks is a topic of significant ethical, cultural, and social relevance. By examining the teachings, scriptures, and historical practices of Islam and Christianity, this research seeks to highlight the similarities and differences in their approaches to animal welfare and rights. The study begins with an overview of the beliefs and attitudes towards animals in both religions. Islamic teachings emphasize the importance of kindness and compassion towards all living beings, reflecting the concept of stewardship over the Earth. Christianity, on the other hand, often draws from the Biblical notion of human dominion over animals while also emphasizing themes of compassion and responsible stewardship. The study will delve into historical and contemporary practices within Islamic and Christian societies, highlighting instances where adherence to or deviation from religious teachings has impacted the treatment of animals. Additionally, the role of religious leaders, scholars, and institutions in shaping attitudes towards animal rights will be examined. It will shed light on how these religions address the moral responsibilities of humans towards the non-human creatures they share the planet with, and how these perspectives have evolved over time. Ultimately, the findings of this research can facilitate discussions on fostering a more compassionate and responsible approach to animal welfare within religious contexts and beyond.